Basic Seasoning Knowlege and Praktice Learning Outcomes: A Correlational Study in Culinary Vocational School - Dhini Alfiani Mursidi; Muhammad Ansori (Universitas Negeri Padang, 2026)
This research aims to analyze the relationship between basic spice understanding and food processing practical learning outcomes among Grade X culinary students at SMK Widya Praja Ungaran. The study employs a quantitative correlational design with a population of 70 students. Data were collected using purposive sampling, selecting 35 students from class X Kuliner 2 as the primary sample after a pilot test on class X Kuliner 1. The instrument for Variable X consisted of 24 valid items (from 30 initial items) with a reliability coefficient (Cronbach's Alpha) of 0.940. Normality testing using Kolmogorov-Smirnov with Monte Carlo simulation confirmed both variables were normally distributed, justifying parametric analysis. Statistical analysis revealed a correlation coefficient (r) of 0.068 with a significance value of 0.699 > 0.05 and a coefficient of determination (R²) of 0.006. These results indicate a positive but non-significant relationship, meaning basic spice understanding contributes only 0.6% to the variation in practical learning outcomes and does not directly determine psychomotor performance in a laboratory setting. These findings suggest that vocational culinary education requires stronger integration between theoretical instruction and repetitive hands-on practice to bridge the cognitive-psychomotor gap.